Foreign Language Listening Anxiety in an Academic Listening Class - Arini Nurul Hidayati; Nita Sari Narulita Dewi; Enjang Nurhaedin; Dewi Rosmala (UIR Press, 2020)
In the process of teaching listening, anxiety is believed as a negative factor contributing to the students’ poor listening comprehension and quite possibly the affective factor that the most persistently hinders the learning process. Thus, investigating its existence and delving its factors become salient in order to help the students overcome their listening learning barriers. This present study attempts to depict the condition of the students’ listening anxiety in an Academic Listening (AL) class in an Indonesian tertiary context. 20-items of Foreign Language Listening Anxiety’s (hereafter, FLLA) questionnaire were administered to 97 students taking that course. Having finished analyzing the levels of students’ listening anxiety, in-depth interviews were conducted to four students who were considered having high listening anxiety to disclose the underlying factors. The research result revealed three pivotal issues; a) 54.6% of the students had a relatively high level of listening anxiety, 18.5% had moderate listening anxiety, and 26.8% had a low level of listening anxiety; b), 75% of the chosen measured items showed an extreme level of the students’ listening anxiety, and c) the major factor contributing the listening anxiety was inadequate listening proficiency involving the inability to deal with the rapid speech rate and range of lexical choices.